COMPLAINT MANAGEMENT PROCEDURE AND CUSTOMER PATRONAGE IN SELECTED TOURISM SITES IN IMO STATE, NIGERIA (Journal of the Management Sciences, 2024)
The study examined complaint management procedure and customer revisit intension/patronage in selected tourism sites in Imo State. The research problem is that the empirical studies accessed by the researchers in the area of complaint management did not handle the relationships which this present study assesses. The study was therefore conducted to examine how attentively listening to customer complaints influences customer revisit intention; assess the relationship between identification of type of complaintcustomer and customer revisit intention; investigate how quick response to customer complaints affects customer patronage; and determine how logging complaint in database influences customer patronage. The study adopted the survey research design. Data were obtained from both primary and secondary sources. The purposive sampling technique was adopted in the study. The Cronbach Alpha statistic was used to obtain a value of 0.77 as the instrument reliability ratio. Data analysis was committed to descriptive statistics and correlation analysis techniques. The results showed that attentively listening to customer complaints influenced customer revisit intention; identification of type of complaintcustomer improved customer revisit intention; quick response to customer complaints enhanced customer patronage and logging complaint in database influenced customer patronage in Imo State. It was concluded that effective complaint management procedure beefed customer revisit intention/patronage in tourism sites in Imo State. The study recommends that management should always listen attentively and professionally to customer complaints and complained-customers should be identified for better management. Also, quick response should be given to customer complaints and complaints should always be logged in database so as to sustain and even increase customer revisit intention/patronage
Keywords: Complaint management procedure, customer patronage, tourism.